ESTUDO DA VARIABILIDADE DA PRECIPITAÇÃO PLUVIAL EM MUNICÍPIOS DA REGIÃO SUL DOS CAMPOS GERAIS, PARANÁ, BRASIL - Maysa de Lima Leite; Patrícia Alves Adacheski; Jorim Sousa das Virgens Filho (Revista Brasileira de Climatologia, 2010)
The aim of this study was to evaluate the characteristics of rainfall in FernandesPinheiro, Lapa, Ponta Grossa, municipal districts in the southern region ofCampos Gerais, Paraná , Brazil, and nearby. Within this context, it wasanalyzed the interannual and seasonal variability of the precipitation, the mostsignificant years inside the series, besides evaluating their intensities and returnperiods. The precipitation was well distributed during the whole year in the three municipal districts, being January the rainiest month, so much in precipitationtotals as in number of days with rain, and August, the less rainy month. Thesprinkle class was the most frequent in Fernandes Pinheiro and Lapa, while inPonta Grossa, the most frequent class was the one of weak rain. The returnperiod for rains with daily totals of 2.5 mm or more, was less than 2 years witha high probability of occurrence for the three locations , while for daily totals of50 mm or more, the return period varied between 17 and 125 years, dependingon the month and of the place.